The concept of the contact angle in the process of oil film formation in internal combustion piston engines - Piotr Wróblewski; Stanisław Kachel (Scientific Reports, 2023)
Abstract In internal combustion piston engines, the process of oil film formation differs from that in industrial machines. The adhesive strength of the molecules at the interface between the coating of engine parts and the lubricating oil affects the load carrying capacity and the ability to form a lubricated film. The geometry of the lubricating wedge between the surfaces of the piston rings and the cylinder wall is determined by the thickness of the oil film and the amount of oil coverage of the ring. This state is modified by many parameters describing the operation of the engine and the physical and chemical parameters of the coatings of the cooperating pairs. For lubricating molecules reaching energies greater than the energy barrier of adhesion at the boundary, sliding occurs. Therefore, the value of the contact angle of the liquid on the surface of the coating depends on the value of the intermolecular force of attraction. According to the author, there is a strong correlation between the contact angle and the lubrication effect. Research indicates that the potential barrier is a function of the contact angle and the contact angle hysteresis (CAH). The innovation of the work consists in the study of the contact angle and CAH in the conditions of thin layers of lubricating oil in cooperation with hydrophilic and hydrophobic coatings. The thickness of the lubricating film was measured under various speed and load conditions using optical interferometry. The study proves that CAH is a better interface parameter to correlate with the effect of hydrodynamic lubrication.